Permainan Mobile Augmented Reality Berbasis Lokasi Untuk Pengenalan Kehidupan Kampus Bagi Mahasiswa Baru Fakultas Ilmu Komputer Universitas Brawijaya - Renno Andika Syawaludin; Wibisono Sukmo Wardhono; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
New college students will feel a significant difference compared to high school life, in both the academic and socio-cultural aspects. To prepare mentally and gives an overview of the learning system and life on campus so it needed the orientation program for new students to accelerate the adaptation to the new environment. In the â€œPengenalan Kehidupan Kampusâ€ (PK2) new students tend to stay in the room, students can enjoy the activities by playing the game while walking around on campus. From that problem created a game media that used for introduction to university life by using mobile devices with Augmented Reality technology. In implementation of game PK2 will be using Unity game engine and camera sensor using Vuforia SDK. On implementation, the pointer on the game will move based on the position of players. There is also mini-game that played using the camera sensor to obtain information of the campus. The information that has been obtained through mini-game can be accessed via â€œensiklopediaâ€ menu in the game. Tests performed include functionality and usability testing. Through functionality testing Filkom: exploration functionality has been going well. Through usability testing obtained reciprocal of the respondents, with an average satisfaction score 4:13 (82.67%).